Masculinity Failure in The Movie Entitled A Raisin in The Sun - Agustina Pujianti; Arielia Yustisiana (Universitas 17 Agustus 1945 Surabaya, 2026)
Failure of masculinity is the behavior of a man who fails to show the biological side of his masculinity by being irresponsible, not having a leadership spirit, and experiencing homosexuality. Therefore, the embodiment of the failure of masculinity occurs in the four male characters in the movie entitled “A Raisin in the Sun”. The research aims to analyze the failure of masculinity experienced by four male characters including Walter Lee, George Murchison, Joseph Asagai, and Carl Lindner, and the impact of the failure of masculinity experienced by those male characters on themselves. This research data was collected by watching movies, looking for subtitles or transcripts, observing transcripts that discuss masculinity failures, identifying data on masculinity failures in the form of hegemonic masculinity, subordinate masculinity, complex masculinity, and marginal masculinity, coding data from transcripts, and finally analyzing masculinity failures. In this research, the theory of patriarchy and masculinity are used, and psychological and sociological approaches are also essentially used to analyze the data. This research uses descriptive qualitative methods including phrases, clauses, words, and sentences. The results of the research found a failure of masculinity in four male characters, including Walter Lee, George Murchison, Joseph Asagai, and Carl Lindner. Second, researchers found the effects of failed masculinity on Walter Lee's character, including depression, emotional suppression, feeling lonely, and lying in the film entitled A Raisin in the Sun. Masculinity is usually shown automatically in the male characters, but this research has found that they fail to do what such masculinity characteristics are supposed to do by them.